2020
DOI: 10.1002/ijop.12728
|View full text |Cite
|
Sign up to set email alerts
|

Educational gains ofin‐personvs. distance learning in primary and secondary schools: A natural experiment during theCOVID‐19 pandemic school closures in Switzerland

Abstract: Using data from a computer‐based formative feedback system, we compare learning gains in the 8 weeks of school closures related to the COVID‐19 pandemic in Switzerland with learning gains in the 8 weeks before these school closures. The school performance in mathematics and language of N = 28,685 pupils is modelled in second‐order piecewise latent growth models with strict measurement invariance for the two periods under investigation. While secondary school pupils remain largely unaffec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
187
3
18

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(244 citation statements)
references
References 56 publications
9
187
3
18
Order By: Relevance
“…Tomasik et al. ( 2020 ) geben einen Überblick zu Befunden aus Forschungstraditionen, die sich mit den Auswirkungen reduzierter oder fehlender Unterrichtszeit auf Schülerleistungen beschäftigen. Unterrichtszeit kann aus unterschiedlichen Gründen variieren oder gänzlich ausfallen; etwa aufgrund von Schülerfehlstunden, Schulferien und Schulschließungen bedingt durch Naturkatastrophen.…”
Section: Theorie- Und Forschungsstandunclassified
See 3 more Smart Citations
“…Tomasik et al. ( 2020 ) geben einen Überblick zu Befunden aus Forschungstraditionen, die sich mit den Auswirkungen reduzierter oder fehlender Unterrichtszeit auf Schülerleistungen beschäftigen. Unterrichtszeit kann aus unterschiedlichen Gründen variieren oder gänzlich ausfallen; etwa aufgrund von Schülerfehlstunden, Schulferien und Schulschließungen bedingt durch Naturkatastrophen.…”
Section: Theorie- Und Forschungsstandunclassified
“…Tomasik et al. ( 2020 ) resümieren, dass Studien zu Schülerfehlstunden und zu Schulschließungen aufgrund von Naturkatastrophen schwache bis starke negative Effekte auf die Leistungsentwicklungen von Schüler*innen beobachten konnten, während Studien zu Effekten von Schulferien und von zwischen den Bildungssystemen variierenden Unterrichtszeiten kaum nennenswerte Unterschiede in den Schülerleistungen feststellen konnten. Ein weiterer Aspekt, der die Lernzeit von Schüler*innen deutlich beeinflussen kann, ist die Hausaufgabenpraxis.…”
Section: Theorie- Und Forschungsstandunclassified
See 2 more Smart Citations
“…Closures can furthermore impact socioeconomic inequalities in differentiation in secondary education, especially when the transition from primary to secondary education happens after periods of closure, or when standardized tests have been cancelled during school closures (15). Swiss research showed that online instruction during school closures was equally as effective as in-school teaching at the secondary level, while primary education was more negatively affected by online instruction (16). Inequalities in tertiary education may also be less strongly affected by closures, as the credentialization process continues.…”
mentioning
confidence: 99%